2018
DOI: 10.4314/ahs.v18i4.35
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach to malaria prevention at household level in rural communities in Wakiso district, Uganda: impact evaluation of a pilot project

Abstract: BackgroundThe integrated approach to malaria prevention, which advocates for the use of several malaria prevention methods at households, is being explored to complement other existing strategies. We implemented a pilot project that promoted the integrated approach to malaria prevention in two rural communities in Wakiso district, Uganda.ObjectivesThis paper presents the impact evaluation findings of the project carried out 2 years after implementation with a focus on changes in knowledge and practices on mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Other studies elsewhere have also shown a high willingness of community members to support malaria control interventions beyond ITNs and IRS [ 39 , 40 ]. Previous concerns and challenges in the use of several malaria prevention interventions holistically have been related to high costs, methods being many hence time consuming, limited knowledge on some methods and potential negative health effects [ 22 , 40 , 41 ]. Similar issues were highlighted in our study which require careful consideration in the design and implementation of the RCT especially as they would influence adoption of practices.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies elsewhere have also shown a high willingness of community members to support malaria control interventions beyond ITNs and IRS [ 39 , 40 ]. Previous concerns and challenges in the use of several malaria prevention interventions holistically have been related to high costs, methods being many hence time consuming, limited knowledge on some methods and potential negative health effects [ 22 , 40 , 41 ]. Similar issues were highlighted in our study which require careful consideration in the design and implementation of the RCT especially as they would influence adoption of practices.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria remains endemic in at least 87 countries in the world, including Tanzania ( National Bureau of Statistics of Tanzania, 2018 ; WHO, 2019 ). Strategies to control the disease involve adoption of integrated vector control methods that mainly involve the use of techniques that target adult mosquitoes such as long-lasting insecticide-treated bed nets and indoor residual spraying ( Musoke et al., 2018 ). However, these methods are challenged by mosquito development of resistance to the commonly used insecticides and changes in biting behaviors ( Corbel et al., 2012 ; Walker et al., 2016 ; Choi and Furnival-Adams, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A treatise on infectious diseases would be incomplete without malaria34; brucellosis35; Candida albicans 36; Culex pipiens ;37,38; antibiotic prescriptions39; and antibiotic resistance with the so called super bugs!40…”
mentioning
confidence: 99%